SISTEM INFORMASI PEMESANAN DESAIN INTERIOR DAN EKSTERIOR BERBASIS WEB PADA CV. RUSH DESAIN KUPANG - Dewi, Putri Sari; Darmawan, Thirza Adristi Chandrakanti Putri; Dama, Julian Excel (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2025)
In the digital era, the need for accessible information systems is increasingly critical. CV. Rush Desain Kupang, specializing in interior and exterior home design, faces challenges in expanding its market due to traditional marketing limitations. This community service aims to develop a web-based platform to streamline design ordering and consultation. The system is developed using the Waterfall methodology, covering requirements analysis, design, implementation, testing, and maintenance. Technologies used include C#, JavaScript, HTML, CSS, and MySQL. Key features include company profile management, design galleries, online consultations, and order forms. Testing is conducted using black-box methods to validate system functionality and User Acceptance Testing (UAT) to assess user needs. Results show that the platform improves efficiency, expands market reach, and enhances customer experience. This system offers a modern and practical marketing solution to support CV. Rush Desain Kupang in managing design services more effectively.